Drug Targeting and Nanomedicine: Lessons Learned from Liver Targeting and Opportunities for Drug Innovation - Anna Salvati; Klaas Poelstra (MDPI AG, 2022)
Drug targeting and nanomedicine are different strategies for improving the delivery of drugs to their target. Several antibodies, immuno-drug conjugates and nanomedicines are already approved and used in clinics, demonstrating the potential of such approaches, including the recent examples of the DNA- and RNA-based vaccines against COVID-19 infections. Nevertheless, targeting remains a major challenge in drug delivery and different aspects of how these objects are processed at organism and cell level still remain unclear, hampering the further development of efficient targeted drugs. In this review, we compare properties and advantages of smaller targeted drug constructs on the one hand, and larger nanomedicines carrying higher drug payload on the other hand. With examples from ongoing research in our Department and experiences from drug delivery to liver fibrosis, we illustrate opportunities in drug targeting and nanomedicine and current challenges that the field needs to address in order to further improve their success.